Diversity of boletaceae in Peninsular Malaysia / Chan Hong Twu - Chan, Hong Twu (2010)
The Boletaceae (Basidiomycetes) s.l. is a large family of putrescent mushrooms with pores. Members of this well-recognized family form one of the largest, critical fungal components of obligate, symbiotic mycorrhizal communities throughout the temperate and tropical forest ecosystems of the world. They are intimately involved with basic ecosystem processes such as nutrient cycling, nutrient uptake, and decomposition of organic matter. Favourable temperature and humidity conditions in Asian tropical forest support a wide diversity of boletes. However, the seasonality of fruiting, short-lived and often solitary fruiting bodies are major problems encountered when documenting their diversity in tropical forests. The diversity of macrofungi in Malaysia is poorly known with only 20 % of mushroom species so far discovered. The earlier records of boletes were by Chipp (1921). Corner (1972) described 140 species of boleti from Peninsular Malaysia of which 100 were new to science. Later, Corner (1974) recorded 20 species of boletes from Borneo among which six were undescribed. Further, Corner (1972) had expected existence of 300 bolete species in Malaysia. Recently, there were reports of new records and clarifications from Malaysia by Lee (2005), Lee and Chang (2003), Lee et al (1997, 2002), Watling and Hollands (1990), Watling and Lee (1995, 1998), Watling et al (1996, 2006) and Watling (1993, 1994, 2000, 2001). In this study, samples were collected at various selected sites in Peninsular Malaysia from 2003 to 2007. Macromorphological and micromorphological features were used to identify the samples to genus and species level. A total of 52 collections of boletes were identified to 30 species from Peninsular Malaysia. Four species are documented as new to science (Afroboletus malaysiancus, Phylloporus megaporinus, Pulveroboletus claroflavus and Tylopilus favo-ballouii). An additional three species are documented as new records for Peninsular Malaysia (Tylopilus plumbeoviolaceus, Tylopilus rubrobrunneus group and Xanthoconium violaceofuscus). Twenty two species reported by other researchers were re-collected and one specimen is yet to be identified to species level.